Periodontal status and its risk factors among young adults of the Sebha city (Libya) - Syed Wali Peeran; A J A Ranjith Singh; G Alagamuthu; P G Naveen Kumar (Wolters Kluwer Medknow Publications, 2013)
Background: The occurrence of periodontal diseases in humans has been a global problem. Certain risk factors affect the initiation, progression, and severity of periodontitis. The present study has been designed to assess the periodontal status in relation to risk factors such as age, gender, oral hygiene practices, and smoking among the young adults of the Sebha city in Libya. Materials and Methods: A cross-sectional study was carried out among 1,255 subjects aged between 18 years and 34 years. 1,006 (80.15%) subjects were females and 249 (19.84%) subjects were males. Data was generated by conducting interview and clinical examination. The periodontal status was assessed by using Community Periodontal Index of Community Periodontal Index of Treatment Needs . The Chi-square test and analysis of variance were used for statistical analysis at 5% level of significance. Results: A total of 89.08% reported the use of toothbrush and toothpaste for cleaning and 10.91% used other aids, such as finger and Siwak. Of the 1,255 subjects, 3.98% were current smokers (all males). Only 4.7% had healthy periodontium (CPI code 1), while majority of 44.30% were detected with calculus (CPI code 2). Nearly 40.63% had shallow pockets (CPI code 3), 6.29% had bleeding (CPI code 1), and 4.06% had deep pockets (CPI code 4). The overall mean CPI score was 2.33 (0.84). Age and gender showed a statistically significant difference with the CPI codes. Conclusion: The result of this study provides baseline information for planning a preventive program. With preventive procedures being implemented at this young age, there is a possibility that the prevalence of periodontal disease will be lesser during adulthood.